2010
DOI: 10.1007/s10545-010-9185-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenylketonuria as a model for protein misfolding diseases and for the development of next generation orphan drugs for patients with inborn errors of metabolism

Abstract: The lecture dedicated to Professor Horst Bickel describes the advances, successes, and opportunities concerning the understanding of the biochemical and molecular basis of phenylketonuria and the innovative treatment strategies introduced for these patients during the last 60 years. These concepts were transferred to other inborn errors of metabolism and led to significant reduction in morbidity and to an improvement in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…However, the subtle structural destabilization of disease-linked PAH variants is also reminiscent of several other genetic diseases, including cystic fibrosis, several lysosomal storage diseases, and certain hereditary cancers (Ahner et al, 2007;Kampmeyer et al, 2017;Mu et al, 2008), where a slight structural destabilization is sufficient to trigger degradation, leading to an insufficient amount the protein. Accordingly, small-molecule stabilizers such as BH 4 may be attractive pharmaceutical agents to alleviate PKU in those patients who carry missense PAH variants that are still partially functional (Erlandsen et al, 2004;Hingorani et al, 2017;Muntau & Gersting, 2010;Pey et al, 2008). Indeed, in vitro studies have shown that many of the variants included here are still enzymatically active (Erlandsen et al, 2004;Gersting et al, 2008), although they display reduced activity compared with the wild-type enzyme (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the subtle structural destabilization of disease-linked PAH variants is also reminiscent of several other genetic diseases, including cystic fibrosis, several lysosomal storage diseases, and certain hereditary cancers (Ahner et al, 2007;Kampmeyer et al, 2017;Mu et al, 2008), where a slight structural destabilization is sufficient to trigger degradation, leading to an insufficient amount the protein. Accordingly, small-molecule stabilizers such as BH 4 may be attractive pharmaceutical agents to alleviate PKU in those patients who carry missense PAH variants that are still partially functional (Erlandsen et al, 2004;Hingorani et al, 2017;Muntau & Gersting, 2010;Pey et al, 2008). Indeed, in vitro studies have shown that many of the variants included here are still enzymatically active (Erlandsen et al, 2004;Gersting et al, 2008), although they display reduced activity compared with the wild-type enzyme (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…These missense variants are fairly evenly spread throughout the PAH sequence (Erlandsen & Stevens, 1999;Figure 1A), indicating that only a small subset of the mutations are expected to directly ablate biochemical activity, for example, by disrupting the active site. Based on in silico predictions (Pey, Stricher, Serrano, & Martinez, 2007;Wettstein et al, 2015) and observations of certain PKU-linked PAH variants being unstable in vitro (Bjorgo, Knappskog, Martinez, Stevens, & Flatmark, 1998;Erlandsen et al, 2004;Gamez et al, 2000;Gjetting, Petersen, Guldberg, & Guttler, 2001;Pey, Desviat, Gamez, Ugarte, & Perez, 2003;Waters, 2003), PKU has, for some PAH variants, been linked with protein destabilization or misfolding (Leandro, Simonsen, Saraste, Leandro, & Flatmark, 2011;Muntau & Gersting, 2010;Muntau, Leandro, Staudigl, Mayer, & Gersting, 2014;Pey et al, 2007). Accordingly, a subset of PAH variants aggregate when expressed in E. coli (Bjorgo et al, 1998;Gamez et al, 2000;Gjetting et al, 2001;Pey et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Focus has been on substrate reduction therapies by targeting GALK1 to decrease galactose-1-phosphate concentrations (48), and recently superoxide dismutase mimics appear to treat a fruit fly model of galactosemia (49). Another therapeutic approach would be to increase the activity of hGALT, either by enzyme replacement therapy or by small-molecule chemical/pharmacological chaperones (31,40,50,51). The latter is the more economical option based on the experience of lysosomal storage disorders (52).…”
Section: Discussionmentioning
confidence: 99%
“…Instead of reducing precursors of "toxic" Phe, i.e. natural protein intake, the aim of this treatment is to increase residual activity of Phe hydroxylase, presumably by a pharmacological chaperone action, and thus to improve Phe tolerance (Muntau and Gersting 2010). In BH4-responsive patients, this treatment allows natural protein consumption to be increased, improving therapy compliance and metabolic control (Burton et al 2010).…”
Section: Introductionmentioning
confidence: 99%